2016
DOI: 10.12710/cardiometry.2016.8.617
|View full text |Cite
|
Sign up to set email alerts
|

New theory of arrhythmia. Conceptual substantiation of arrhythmia mechanisms.

Abstract: AimsA new attempt is made to substantiate the concept of the mechanism of arrhythmia and sudden cardiac death. MethodsThe paper is based on a theoretical analysis of special literature, personal experience of participation in conferences and discussions with leading Russian cardiologists. ResultsWe have succeeded in demonstrating the fact that researchers ignore the fact that cardiomyocytes can be excited by mechanical pulses, when considering the arrhythmia mechanisms. We have conducted trials using the Cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 3 publications
(3 reference statements)
0
15
0
Order By: Relevance
“…These vessels even with venous valves are not capable of withstanding high pressure, so the liquid sooner or later runs into the extracellular space, and even occupies the free space between the bodies. There are cardiac arrhythmia due to run the pulse wave on the vena cava, and a mechanical pulse effects on the myocardium, except you experience swelling, stagnation, weight gain, "heart failure", varices, ascites [5][6][7]. On the other hand, due to the reduced at the open AVA gradient pressure between arterioles and venules occurs deceleration capillary circulation, cells do not receive power, stagnant blood becomes thicker lymph movement also slows critical drop strength immunity in stagnant fluid activated viruses and parasites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These vessels even with venous valves are not capable of withstanding high pressure, so the liquid sooner or later runs into the extracellular space, and even occupies the free space between the bodies. There are cardiac arrhythmia due to run the pulse wave on the vena cava, and a mechanical pulse effects on the myocardium, except you experience swelling, stagnation, weight gain, "heart failure", varices, ascites [5][6][7]. On the other hand, due to the reduced at the open AVA gradient pressure between arterioles and venules occurs deceleration capillary circulation, cells do not receive power, stagnant blood becomes thicker lymph movement also slows critical drop strength immunity in stagnant fluid activated viruses and parasites.…”
Section: Resultsmentioning
confidence: 99%
“…A role in the development of pelvic congestion has a hormonal influence, raising the level of estrogen, which in turn contribute to the expansion of the diameter of the pelvic veins. Now, with the new knowledge about the causes of venous plethora of causes arrhythmia, a pathological role anastomoses AVA, apparently, in the near future we can expect a breakthrough in the understanding of the etiology of many cardiovascular diseases, among the many problems associated with the increased venous pressure [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…Earlier work has shown some fundamental role arteriovenous anastomoses (AVA) in the mechanism of occurrence of cardiac arrhythmias and other diseases [10][11][12][13][14][15]. It has been shown that the de fitness of the organism during periods of increased physical and nervous stress, due to the short-term or persistent high blood pressure (BP) in humans can be opened AVA.…”
Section: The New Point Of View In Accordance With the New Causes Of Vmentioning
confidence: 99%
“…Let us emphasize that this breakthrough, achieved at least for the last 30 years, was achieved by official medicine, not by a theory, not analytically, but by trial and error with the testing of the effect of various drugs (chemicals) on large groups of patients. But on the other hand, this important message is an additional argument in favor of the New Theory of CVD [4][5][6][7][8][9][10][11][12][13][14][15][16][17], which I have been promoting since 2011. Discovery of scientists from Harvard is an additional argument in understanding the mechanism of tissue perfusion reduction and blood stasis, which, apparently, in itself leads to many CVD.…”
Section: Introductionmentioning
confidence: 99%